Pembelajaran Matematika dengan Media Quipper School - Andi Amza; Muhammad Kristiawan; Happy Fitria (Jurnal Pendidikan Matematika RAFA, 2020)
The purpose of this study was to determine the impact of quipper school media at MTs 1 in Palembang, especially for students who attended class VII to learn mathematics was the purpose of this study. This study uses a quantitative and qualitative descriptive meth-od (mixed method). The results obtained from the implementation of this research are in terms of each indicator, it is stated that the quipper school learning media can be used in mathematics learning to optimize learning activities and it is stated that it helps improve learning outcomes. The teacher who teaches states that the quipper school learning media is effective in learning mathematics to increase the learning activity of students. The results of the observations made by the researchers stated that there was an impact on the application of quipper school learning media at MTs in Palembang, especially in Mathematics for grade VII. It was proof by the increase in the average value of student learning activeness after learning mathematics using the quipper school media.